Single atom devices by ion implantation. (18th March 2015) - van Donkelaar, Jessica; Yang, C; Alves, A D C; McCallum, J C; Hougaard, C; Johnson, B C; Hudson, F E; Dzurak, A S; Morello, A; Spemann, D; Jamieson, D N
Abstract: To expand the capabilities of semiconductor devices for new functions exploiting the quantum states of single donors or other impurity atoms requires a deterministic fabrication method. Ion implantation is a standard tool of the semiconductor industry and we have developed pathways to deterministic ion implantation to address this challenge. Although ion straggling limits the precision with which atoms can be positioned, for single atom devices it is possible to use post-implantation techniques to locate favourably placed atoms in devices for control and readout. However, large-scale devices will require improved precision. We examine here how the method of ion beam induced charge, already demonstrated for the deterministic ion implantation of 14 keV P donor atoms in silicon, can be used to implant a non-Poisson distribution of ions in silicon. Further, we demonstrate the method can be developed to higher precision by the incorporation of new deterministic ion implantation strategies that employ on-chip detectors with internal charge gain. In a silicon device we show a pulse height spectrum for 14 keV P ion impact that shows an internal gain of 3 that has the potential of allowing deterministic implantation of sub-14 keV P ions with reduced straggling.